Integrated Approach to Improve Hemoglobin in Adolescent Girls: A Quasi-Experimental Controlled Study - Dewi Erna Marisa; Erida Fadila; Ahmad Syaripudin; Hasril Desiathul Hamdani; Lily Wahyuni; Tantri Maulani Putri (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2026)
Introduction: A major public health issue affecting adolescent girls is anemia, largely as a result of insufficient iron intake, menstrual blood loss, and poor nutritional literacy. A single-component intervention either supplementation or education rarely produces more than a modest amelioration. Evaluating the effectiveness rates of an integrated intervention, consisting of an iron-rich diet as a component of the regimen, iron supplementation as supplementary factor, and structured nutritional education versus single-component strategies aimed to improve hemoglobin (Hb) among adolescent girls, this study aims to address limitations associated with a single-component intervention approach alone. Methods: A quasi-experimental controlled non-randomized design with prospective follow-up was carried out with 180 adolescent girls between 12–18 years of age recruited from a stratified sampling. Participants were recruited in school and divided into three intervention arms to reduce contamination. In addition to the oral iron supplementation (60 mg, two times weekly for 12 weeks), the intervention utilized iron-rich dietary intervention, and included six structured education sessions based on the Health Belief Model. Hemoglobin levels were measured at baseline, Month 3, and Month 6 using the cyanmethemoglobin method. Dietary behaviour and adherence were assessed on the basis of validated instruments. Data were analyzed using repeated measures ANOVA and assumption diagnostics with appropriate revisions, Tukey post-hoc comparisons and multivariate linear regression adjusted for baseline Hb and all relevant covariates. Statistical significance was defined as p < 0.05. Results: No differences between baseline hemoglobin levels (p = 0.632). All intervention arms showed significant increases of Hb over six months (time effect, p < 0.001). The integrated intervention achieved the most mean improvement (3.5 g/dL) than supplementation plus education (2.2 g/dL) and diet plus education (1.6 g/dL) and there were significant (p < 0.001) between-group differences. Intervention type and adherence level were still significant predictors of hemoglobin improvement in adjusted regression analysis. Conclusion: The integrated intervention showed superior comparative efficacy compared with single-component approaches in improving hemoglobin levels among adolescent girls. The recommendations of this study are supported by evidence based on evidence-based, multi-component, and structured in school prevention and control programs in the development of adolescent health policies.